2016
DOI: 10.1155/2016/9534063
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Kinetic Modelling of Wheat Straw from the Pannonian Region

Abstract: The pyrolysis/devolatilization is a basic step of thermochemical processes and requires fundamental characterization. In this paper, the kinetic model of pyrolysis is specified as a one-step global reaction. This type of reaction is used to describe the thermal degradation of wheat straw samples by measuring rates of mass loss of solid matter at a linear increase in temperature. The mentioned experiments were carried out using a derivatograph in an open-air environment. The influence of different factors was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The proximate analysis of rice straw is compared with wheat straw and sugarcane bagasse (Table ). It showed that ash and silica content of rice straw is significantly higher in comparison to wheat straw and sugarcane bagasse …”
Section: Rice Straw Structural Constituents and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximate analysis of rice straw is compared with wheat straw and sugarcane bagasse (Table ). It showed that ash and silica content of rice straw is significantly higher in comparison to wheat straw and sugarcane bagasse …”
Section: Rice Straw Structural Constituents and Characteristicsmentioning
confidence: 99%
“…It showed that ash and silica content of rice straw is signifi cantly higher in comparison to wheat straw and sugarcane bagasse. [47][48][49][50][51][52][53][54]…”
Section: Rice Straw Structural Constituents and Characteristicsmentioning
confidence: 99%
“…Pešenjanski et al [4] used a one-step global reaction to describe the thermal degradation of wheat straw samples. The influence of different factors was investigated, such as particle size, humidity levels and the heating rate in the kinetics of devolatilization.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations concerning the beet pulp and straw pyrolysis were carried out using different methods. Most of them were performed using laboratory analytical equipment, where biomass weight micro samples were used as the substrate [ 28 , 29 , 30 ]. Additionally, using micro samples and applying the Thermogravimetric Analysis (TGA) method, the kinetics of pyrolysis of beet pulp, separated or mixed with lignite, was studied [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%